Moral reasoning through the eyes of persons with behavioral variant frontotemporal dementia - Antoniou, Rea; Hausermann, Tobias; Sideman, Alissa Bernstein; Fong, Kristina Celeste; Callahan, Patrick; Miller, Bruce L.; Kramer, Joel H.; Chiong, Winston; Rankin, Katherine P. (Frontiers in Neurology, 2023)
Persons with behavioral variant frontotemporal dementia (bvFTD) exhibit antisocial tendencies. An example of this tendency is adopting utilitarian choices towards sacrificial moral dilemmas which engage harmful actions to promote overall welfare. Moral cognition models interpret such tendencies as deriving from a lack of emotional engagement and selective impairment in prosocial sentiments. We applied a qualitative approach to test those theoretical assumptions and to further explore the emotional experiences and values of people with bvFTD while they contemplate moral scenarios. We conducted semi-structured interviews with 14 participants: 7 persons with bvFTD and 7 older healthy controls. Transcripts were coded using ATLAS.ti 5.0. During moral reasoning, persons with bvFTD reported more positive emotions than negative and showed significantly less cognitive precision in their moral reasoning compared to controls. Persons with bvFTD also organized their choices predominantly around kindness and altruism, and their responses reflected higher rule compliance. Our study showed that bvFTD persons’ utilitarian responses to moral dilemmas did not arise from an emotionally flat or antisocial perspective. Instead, they were underpinned by positive emotionality and prosocial values. These findings enrich current understandings of moral cognition and highlight the importance of incorporating mixed methods approaches in dementia research that take into consideration the viewpoint of cognitively impaired individuals.